The Mediating Effect of Transparency on the Relationship Between Digitalization and Revenue Generation, Public Participation, and Allocation Efficiency - Oti-Akenteng, Ernest; Ocansey, Evans O. N. D.; Asamoah, Felix Oppong (Archives of Business Research, 2025)
This study investigates the mediating role of transparency in the relationship between digitalization and three critical governance outcomes: revenue generation, public participation, and allocation efficiency within the context of local governments in Ghana. While digital transformation has been widely promoted as a solution to inefficiencies in public sector management, empirical evidence on its effectiveness—particularly when transparency is considered—remains limited in sub-Saharan African contexts. The main objective of the study is to examine whether transparency acts as a conduit through which digitalization improves fiscal performance, citizen engagement, and resource distribution. It also aims to assess the extent to which institutional quality and political stability influence these relationships. The study adopts a quantitative research design, using secondary panel data from 2010 to 2022 sourced from the World Bank, Bank of Ghana, and Our World in Data. Statistical analyses—including regression modeling and mediation analysis—were performed using EViews 12 to test the direct and indirect effects of digitalization on the dependent variables. The findings reveal that transparency significantly mediates the relationship between digitalization and both revenue generation and allocation efficiency, while its effect on public participation is unexpectedly negative, suggesting a disconnect between formal transparency efforts and citizen engagement. Digitalization alone was found to have no direct significant impact on any of the three outcomes, underscoring the importance of institutional context and information accessibility. These results offer practical implications for governance reforms, emphasizing the need for digital strategies to be embedded within transparent, participatory, and user-centered frameworks. The study also contributes to accounting and public administration literature by positioning transparency as a vital link between digital innovation and governance outcomes